Wiedenbach Need for Help and Swanson Caring Model on Nursing Care of Prolonged Second Stage of Labour - Susanti, Henny Dwi (University of Muhammadiyah Malang, 2016)
The second stage of labour is defined as the period from full dilatation of the cervix to the birth of the baby. Prolonged Second Stage of labour greater than 2 hours in primiparous women and greater than 1 hours in multiparous. Nursing management for women with prolonged second stage of labour is providing nursing care both physical and psychological aspec. Case study focused on Wiedenbach Need for Help and Swanson Caring Model on nursing care of prolonged second stage of labour. Applications of Swanson and Wiedenbach theory are implemented and managed to help problem solving for 5 mothers case with prolonged second stage of labour. Therefore nursing emergency action must be done properly and quickly by using the theory of